The Cytochrome bd Complex Is Essential for Chromate and Sulfide Resistance and Is Regulated by a GbsR-Type Regulator, CydE, in Alishewanella Sp. WH16-1 - Xia, Xian; Wu, Shijuan; Li, Liqiong; Xu, Biao; Wang, Gejiao (Frontiers in Microbiology, 2018)
Sulfate-reducing bacteria are a group of microorganisms that use sulfate as an electron acceptor. These bacteria are useful in the bioremediation of heavy metal pollution since they can reduce/precipitate metals. Previously, we identified the Alishewanella strain WH16-1 from soil of a copper and iron mine and determined that it can reduce sulfate and chromate and that it was tolerant to many heavy metals. In this study, we investigated the chromate reduction mechanism of strain WH16-1 through Tn5 transposon mutagenesis. A cytochrome bd (cytbd) Tn5 mutant was generated (△cytbd), and a detail analysis showed that the following: (1) gene cydE (coding for a GbsR-type regulator) was co-transcribed with the two subunits coding genes of the Cytochrome bd complex (Cytbd), namely, cydA and cydB, based on RT-PCR analysis, and similar gene arrangements were also found in other Alteromonadaceae family strains; (2) the chromate resistance level was dramatically decreased and chromate reduction efficiency also decreased in strain △cytbd compared to the wild type and a complemented strain (△cytbd-C); (3) Cytbd could catalyze the decomposition of H2O2 according to the analyses of H2O2 decomposition ability, cellular H2O2 contents, H2O2 inhibition zone and H2O2 sensitivity tests; (4) surprisingly, chromate was not an inducer of the expression of Cytbd, but sulfate induced expression of Cytbd, and sulfate/sulfide resistance levels were also decreased in the △cytbd strain; (5) the addition of sulfate enhanced the chromate resistance level and reduction efficiency; (6) Cytbd expression was repressed by CydE and derepressed by sulfate based on an in vivo bacterial one hybrid system and in vitro EMSA tests; and (7) DNA footprinting and short-fragment EMSA tests revealed two binding sites of CydE in its promoter region. All these results showed that Cytbd is negatively regulated by CydE and derepressed by sulfate. In addition, Cytbd contributes to the resistance of sulfate and sulfide, and sulfide could be used as a reductant to reduce chromate. Moreover, Cytbd is essential to decompose H2O2 to decrease cellular oxidative stress. Thus, the regulation and function of Cytbd may explain why sulfate could enhance chromate reduction.